TECHNICAL SECURITY IN ITE LAW AND COPYRIGHTS OF DEVICES AND SYSTEMS - Septian Rizky Dalimunthe; Sri Anisa Pujawati; Akmal Satria Alvin Sitorus (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
Copyright is the creator's or recipient's exclusive right to publish or reproduce his work, or to grant permission to do so, without reducing the restrictions imposed by applicable laws and regulations. This research aims to determine how the legal protection of creators for the use of illegal software is based on the Copyrights Law No. 19 of 2002. The study employs normative law research methods, as well as secondary data obtained through library research. According to the findings, product piracy costs the creator both financially and morally, as well as having an economic impact on the country. Aside from that, using pirated software raises a fatal risk because malware/viruses can easily infiltrate software, opening the way for cyber attacks. As a consequence, it is recommended that legal proprietary software be used for work, learning, or other software-related activities. If people are unable to obtain legal software due to a lack of resources, they should consider other options, such as open source software that is available for free. Furthermore, proprietary software (closed) vendors must be able to offer reasonable prices. If a person or company infringes on another's copyright, they could face criminal charges or civil lawsuits.